Students’ Perceptions of English for Tourism Purposes: Importance, Motivation, and Challenges in Learning - Ririn Pratiwi Suharto; Putri Sekarsari (IKIP Siliwangi, 2026)
This study examined tourism students’ perceptions of the importance of English for tourism purposes, their motivation in learning English, and the challenges they faced during the learning process. The participants of this study were 40 tourism students from a vocational school or university who were actively learning English for tourism. The study used a descriptive qualitative approach. Data were collected through a questionnaire consisting of statements related to the importance of English, students’ motivation, and learning challenges. The responses were measured using a Likert scale and analyzed in percentages to describe the students’ overall views. The results showed that students had a very strong perception of the importance of English for tourism purposes. They were also highly motivated to learn English, mainly because of their future careers, interest in tourism topics, and desire to improve their speaking skills. However, students still experienced several challenges, especially in vocabulary, pronunciation, grammar, and speaking confidence. In conclusion, although students showed positive attitudes and strong motivation, there was still a gap between their awareness of English and their ability to use it confidently in real communication. Therefore, more interactive and practical English learning activities are needed to support their future tourism careers.